Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.3 Logarithmic Functions - 6.3 Exercises - Page 427: 35



Work Step by Step

Solve each equation for $x$. Given: $e^{2x}-e^{x}-6=0$ $(e^{x}+2)(e^{x}-3)=0$ Thus, $e^{x}=3$ or $e^{x}=-2$ Consider positive term we have $e^{x}=3$ This implies $x=ln3$ Hence, $x=ln3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.